ANALISIS PENERAPAN PSAK NO. 23 TENTANG PENDAPATAN PADA PT. PEGADAIAN CABANG MEGAMAS MANADO - Musadi, Claudia Relia; Karamoy, Herman; Gamaliel, Hendrik (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Revenue is one of the most important elements of the formation of income statement within a company. Revenue is due to the companys activities in utilizing production factors for self-sustaining and growth. This research was conducted at PT. Pegadaian Cabang Megamas Manado, a company engaged in financial services whose main activity is to disburse loan money on the basis of legal lien. The purpose of this study is to analyze the process of recognition, pemgukuran, and disclosure of income from PT. Pegadaian Cabang Megamas Manado by using PSAK No. 23 on Revenue as a comparison. The method used is qualitative research method, that is descriptive analysis. The results showed, the recognition of income at PT. Pegadaian Cabang Megamas Manado is recognized based on accrual basis in which income is recognized upon acquisition of goods or services. The measurement of income is recorded at the amount of cash received or at fair value provided for the income. Revenue disclosures are made on the basis of each income post. Recognition, measurement, and disclosure of income at PT. Pegadaian Cabang Megamas Manado is in accordance with PSAK No. 23.Keywords: Â Revenue, Recognition, Measurement, Disclosure